Imaging neural activity in the ventral nerve cord of behaving adult Drosophila. Issue 1 (December 2018) - Chen, Chin-Lin; Hermans, Laura; Viswanathan, Meera; Fortun, Denis; Aymanns, Florian; Unser, Michael; Cammarato, Anthony; Dickinson, Michael; Ramdya, Pavan
Abstract To understand neural circuits that control limbs, one must measure their activity during behavior. Until now this goal has been challenging, because limb premotor and motor circuits have been largely inaccessible for large-scale recordings in intact, moving animals—a constraint that is true for both vertebrate and invertebrate models. Here, we introduce a method for 2-photon functional imaging from the ventral nerve cord (VNC) of behaving adultDrosophila melanogaster . We use this method to reveal patterns of activity across nerve cord populations during grooming and walking and to uncover the functional encoding of moonwalker ascending neurons (MANs), moonwalker descending neurons (MDNs), and a previously uncharacterized class of locomotion-associated A1 descending neurons. Finally, we develop a genetic reagent to destroy the indirect flight muscles and to facilitate experimental access to the VNC. Taken together, these approaches enable the direct investigation of circuits associated with complex limb movements. TheDrosophila ventral nerve cord (VNC) is functionally equivalent to the vertebrate spinal cord. This study reports a 2-photon imaging approach for recording neural activity in the VNC of walking and grooming adult flies.